Does Downward Accountability Work? An Assessment of Local Governance Practices in Nepal - Shahi, Min Bahadur; Kharel, Suman; Pradhan, Prajwal Man (Nepalese Journal of Development and Rural Studies, 2023)
The articulation of downward (social) accountability to the local government (LG) has been established by the new constitution of Nepal (2015) and further elaborated in the Local Government Operational Act (2017). LGs in Nepal have gained more autonomy, role, and responsibility for providing public services to local citizens following the state restructuring into federal Nepal. What does local governance practice look like today in terms of downward accountability? This paper examines the existing patterns of downward accountability, particularly in the same cases of local government in the Kailali district in the Sudurpaschim Province. Two separate field-based studies were conducted in different periods. Initially, the study assessed the compliance of social accountability tools in three local units (2019). The second attempt was a study focused on the practices of the monitoring mechanisms of four LG units (2021). The analysisused the observation check-list, key informant interview, and questionnaire schedule for data collection. The respondents to the study were the elected representatives, staff of LGs, and service-receiving citizens. This observation shows doubt about the practice of downward accountability at LG and its compliance, which appears to be ambiguous. LG elected representative’s perception of downward accountability and the compliance mechanism must be clarified and specific. However, both elected representatives and the citizens have taken monitoring action in support of the downward accountability of LG. Effective service delivery has slowed due to a lack of a standardized downward accountability system.